(untitled) (Journal of Partial Differential Equations, 1998)
The continuous casting Stefan problem is a mathematical model describing the solidification with convection of a material being cast continuously with a prescribed velocity. We propose a practical piecewise linear finite element scheme motivated by the characteristic finite element method and derive an error estimate for the scheme which is of the same convergence order as that proved for Stefan problem without convection.